Adaptación y validación de la versión chilena del Cuestionario Evaluación de la Atención de Enfermedades Crónicas, cliente externo - Lagos G, Maria Elena; Salazar M, Alide; Salas F, Patricio (Revista Médica de Chile, 2017)
Background: The Patient Assessment of Chronic Illness Care (PACIC) questionnaire is a widely used instrument to assess chronic disease care from a patient’s perspective. Aim: To adapt the PACIC questionnaire to Chilean Spanish and to evaluate the psychometric properties of the translation. Material and methods: Descriptive, cross-sectional design with exploratory and confirmatory factor analysis. The PACIC questionnaire was applied, throughout an external client, to 200 users who received health care at the cardiovascular program in a Family Health Center in Concepción, Chile. Results: The confirmatory factor analysis did not show a good adjustment with the proposed structure in the original instrument. An exploratory factor analysis revealed five factors explaining 58% of total data variability. The distribution of the factor-items of the original questionnaire underwent some modifications, which are explained when analyzing the theoretical construct. A good reliability of the global scale was obtained (Cronbach’s ? 0.886). Conclusions: The PACIC questionnaire, Chilean version does not replicate the proposed structure of the original questionnaire. Therefore, further research about its validity, incorporating a higher number or diversity of participants is recommended.